Lipiodol retention pattern predicts transarterial chemoembolization therapeutic effect in hepatocellular carcinoma - Margaretha Vianny; Gunawan Santosa; Eddy Soedijanto (Universa Medicina, 2015)
BACKGROUND Hepatocellular carcinoma (HCC) incidence is increasing in Asia and Africa. Locoregional minimally invasive transarterial chemoembolization (TACE) is the palliative therapy of choice, improving survival rate. Adequate lipiodol dose calculation in TACE is necessary to produce good therapeutic effect. Lipiodol retention pattern can predict TACE therapeutic effect. This study aimed to determine correlation of lipiodol volume/tumor volume (L/V) ratio and lipiodol volume/tumor diameter (L/D) ratio with lipiodol retention pattern in post-TACE CT-scans of HCC patients. METHODS This cohort prospective study was done from November 2013 to March 2014 on eighteen HCC patients with post-TACE therapy in Dr.Kariadi Hospital, Semarang, fullfilling inclusion and exclusion criteria. Lipiodol retention pattern was observed on 28 days post-TACE and classified as type I (lipiodol accumulation in tumor and surrounding area), type II (homogenous accumulation in tumor only), and type III (partial accumulation). The Spearman correlation test was used to determine any relationships between the various variables studied. RESULTS Spearman correlation test showed that lipiodol volume had significant moderate correlation with lipiodol retention pattern (r=-0.684; p=0.002). Both L/V and L/D ratios had moderately significant correlation with lipiodol retention pattern (r=0.511; p=0.030; and r=0.518; p=0.028, respectively). CONCLUSION Correlations of L/V ratio L/D ratio with lipiodol retention pattern were both moderately significant. Lipiodol dose calculation based on L/V ratio is suggested considering the irregular three-dimensional form of the tumor, making volumetric measurement more appropriate.